Depth Estimation of Vertical Dyke by Applying a Simple Equation - Al-Rawi , Fitian R.; Al-Yasi , Ameen I.; Al-Mosawi , Walaa M. (Iraqi Journal of Science, 2021)
A new procedure of depth estimation to the apex of dyke-like sources frommagnetic data has been achieved through the application of a derived equation. Theprocedure consists of applying a simple filtering technique to the total magneticintensity data profiles resulting from dyke-like bodies, having various depths, widthsand inclination angles. A background trending line is drawn for the filtered profileand the output profile is considered for further calculations.Two straight lines are drawn along the maximum slopes of the filtered profileflanks. Then, the horizontal distances between the two lines at various amplitudelevels are measured and plotted against the amplitudes and the resulted relation is asloping line. The constant values of the equation of the least square fitting to theslope line and with the maximum value of the filtered profile multiplied by anempirical factor have been used to determine the depth to dyke-like source. Lowerrors percentages have been obtained from the application of the present procedureto a large number of dyke-like bodies and to the field example, indicating thesuccessful of the method.